Personalized statistical modeling of soft tissue structures in the knee - Van Oevelen, A.; Duquesne, K.; Peiffer, M.; Grammens, J.; Burssens, A.; Chevalier, A.; Steenackers, G.; Victor, J.; Audenaert, E. (Frontiers in Bioengineering and Biotechnology, 2023)
Background and Objective: As in-vivo measurements of knee joint contact forces remain challenging, computational musculoskeletal modeling has been popularized as an encouraging solution for non-invasive estimation of joint mechanic loading. Computational musculoskeletal modeling typically relies on laborious manual segmentation as it requires reliable osseous and soft tissue geometry. To improve on feasibility and accuracy of patient-specific geometry predictions, a generic computational approach that can easily be scaled, morphed and fitted to patient-specific knee joint anatomy is presented. Methods: A personalized prediction algorithm was established to derive soft tissue geometry of the knee, originating solely from skeletal anatomy. Based on a MRI dataset (n = 53), manual identification of soft-tissue anatomy and landmarks served as input for our model by use of geometric morphometrics. Topographic distance maps were generated for cartilage thickness predictions. Meniscal modeling relied on wrapping a triangular geometry with varying height and width from the anterior to the posterior root. Elastic mesh wrapping was applied for ligamentous and patellar tendon path modeling. Leave-one-out validation experiments were conducted for accuracy assessment. Results: The Root Mean Square Error (RMSE) for the cartilage layers of the medial tibial plateau, the lateral tibial plateau, the femur and the patella equaled respectively 0.32 mm (range 0.14-0.48), 0.35 mm (range 0.16-0.53), 0.39 mm (range 0.15-0.80) and 0.75 mm (range 0.16-1.11). Similarly, the RMSE equaled respectively 1.16 mm (range 0.99-1.59), 0.91 mm (0.75-1.33), 2.93 mm (range 1.85-4.66) and 2.04 mm (1.88-3.29), calculated over the course of the anterior cruciate ligament, posterior cruciate ligament, the medial and the lateral meniscus. Conclusions: A methodological workflow is presented for patient-specific, morphological knee joint modeling, avoiding laborious segmentation. By allowing to accurately predict personalized geometry, this method has the potential for generating large (virtual) sample sizes applicable for biomechanical research and improving personalized, computer-assisted medicine.